Small state strategies in emerging regional governance structures: explaining the Danish advocacy for China's inclusion in the Arctic Council. Issue 1 (1st January 2018) - Kluth, Michael; Lynggaard, Kennet
ABSTRACT: This article departs from the puzzling observation that of the five littoral arctic states the Danish realm has been the most consistent backer in China's quest to gain observer status in the Arctic Council. Small states are generally assumed to adapt to changes in the international system such as spatial re-configurations and alterations in the distribution of capabilities. Yet Denmark's enabling role in relation to China seems to contravene that assumption. Why would a small state invite one of the world's leading powers to enter its regional domain while its principle allies and regional partners – including USA and Canada – were still indecisive or outright hesitant? This article explores three possible explanations for the Danish support for China: 1) a domestic politics explanation featuring strategic use of discourse to entice Chinese investments in Arctic mineral extraction. 2) a securitisation explanation suggesting that unease with growing Canadian securitisation of Arctic issues has prompted courting China as a balancing act. 3) a foreign policy identity explanation focussing on the normative desire to enmeshment China into a liberal Arctic order.